Tissue factor antigen is elevated in patients with microvascular complications of diabetes mellitus - Klevesath, Martina; Hofmann Bowman, Marion; Borcea, Valentin; Luther, Th; Kotzsch, M.; Müller, M.; Hergesell, Olaf; Andrassy, Konrad; Ritz, Eberhard; Ziegler, Reinhard; Wahl, Peter; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 1997)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 14. Julli 2009
Gesehen am 02.11.2023